The level of children's language skills from the teachers' point of view (A field study in the city of latakia) - حمدان, ندى; عبير حاتم (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
The aim of the research is to identify the level of language skills among children from the point of view of female teachers in the city of latakia, according to the variables (academic qualification- number of years of experience). To achieve the objectives of the research, the researcher developed a language skills questionnaire consisting of (28) items distributed over four main dimensions, and it was confirmed that its validity and reliability were then applied to a sample of (46) third-grade teachers in private kindergartens in the city of latakia. The results showed that: the level of children's language skills from the teachers' point of view is high, and it also showed that there were statistically significant differences between the average scores of the teachers on the research tool was based on (academic qualification- number of years of experience). And in light of the research results, the research presented several suggestions.